Mental Life without Concepts and Animal Cognition in Kant´s Philosophy - Stepanenko Gutiérrez, Pedro (Con-Textos Kantianos. International Journal of Philosophy, 2023)
According to a conceptualist interpretation of Kant’s theoretical philosophy the use of concepts is a necessary condition for perception. A frequent objection of the Kantian non-conceptualists against this idea points out that Kant accepted perceptions without concepts because he denied that non-human animals have concepts. This paper aims to answer that objection by showing that for Kant the mental life of non-human animals, that is, a mental life without concepts, is only a natural mechanism by which behavioral responses are related to stimuli like sensations, where no representations of objects take place stricto sensu.